2019
DOI: 10.1038/s41467-019-12482-1
|View full text |Cite|
|
Sign up to set email alerts
|

TFPa/HADHA is required for fatty acid beta-oxidation and cardiolipin re-modeling in human cardiomyocytes

Abstract: Mitochondrial trifunctional protein deficiency, due to mutations in hydratase subunit A (HADHA), results in sudden infant death syndrome with no cure. To reveal the disease etiology, we generated stem cell-derived cardiomyocytes from HADHA-deficient hiPSCs and accelerated their maturation via an engineered microRNA maturation cocktail that upregulated the epigenetic regulator, HOPX.  Here we report, matured HADHA mutant cardiomyocytes treated with an endogenous mixture of fatty acids manifest the disease pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 103 publications
1
71
0
Order By: Relevance
“…Quantitative RT‐PCR analysis identified a set of upregulated PPARγ target genes, including Fabp4 , Ncoa4 , Pparg , and Zfml in Hes1 f/f Vav1Cre LSK cells compared to those from Hes1 f/f mice (Figure A). Since PPARγ is the master regulator in FAO metabolic pathway, we also observed a panel of upregulated FAO related genes, such as Slc25a20 , Hadha , Cpt1a , Cpt2 (Figure B). We next assessed FAO rates and found that Hes1 deletion significantly increased FAO in LSK cells isolated from Hes1 f/f Vav1Cre mice compared to those from Hes1 f/f mice as determined by the palmitate oxidation method (Figure C).…”
Section: Resultsmentioning
confidence: 86%
“…Quantitative RT‐PCR analysis identified a set of upregulated PPARγ target genes, including Fabp4 , Ncoa4 , Pparg , and Zfml in Hes1 f/f Vav1Cre LSK cells compared to those from Hes1 f/f mice (Figure A). Since PPARγ is the master regulator in FAO metabolic pathway, we also observed a panel of upregulated FAO related genes, such as Slc25a20 , Hadha , Cpt1a , Cpt2 (Figure B). We next assessed FAO rates and found that Hes1 deletion significantly increased FAO in LSK cells isolated from Hes1 f/f Vav1Cre mice compared to those from Hes1 f/f mice as determined by the palmitate oxidation method (Figure C).…”
Section: Resultsmentioning
confidence: 86%
“…Studies have shown that proton leak through ADT was elevated in aged mitochondria and impairment of ADT was believed to play a central mechanism causing aged-related mitochondria defects [66][67][68]. More significantly, a recent report showed that mitochondrial trifunctional enzyme-deficient cardiac model system that simulates SIDS disease had a higher level proton leak and SS-31 treatment rescued the increased proton leak [69]; another recent report showed that SS-31 can suppress proton leak and rejuvenate mitochondrial function through direct binding with ADT [70]. SS-31 shares many common properties with inhibitors BKA and CATR such as larger molecular volume than ADP or ATP, and binding with ADT via multiple polar interactions [64]; and additionally, all three molecules were reported to block proton leak in ADT [70].…”
Section: Atp Production and Transport (Cv Ck And Adt)mentioning
confidence: 99%
“…5). Interestingly SS-31 was recently shown to rescue excessive proton leak in cardiomyocytes with mutated ECHA [69].…”
Section: Trifunctional Enzymementioning
confidence: 99%
“…Microposts can be a versatile tool for measuring cellular forces. With immunofluorescent techniques, they have been used to examine signaling pathways that regulate cell–matrix forces and focal adhesion size Using optical microscopy for live cell imaging, they can be used to quantify the dynamics of twitch contractions in neonatal rat cardiomyocytes and pluripotent stem cell‐derived cardiomyocytes . Microposts can also be used to measure the forces of platelet aggregates that form on the tips of microposts in an effort to understand the mechanisms that regulate thrombus formation .…”
Section: Deformable Structuresmentioning
confidence: 99%